For two angles a and b tan(a - b) = (tan a - tan b)/(1 + tan a*tan b)

Now in (tan(x+y) - tan y)/(1 + tan(x+y)*tan y) take x + y as a and y as b

=> (tan a - tan b)/(1 + tan a*tan b)

This is the same as tan (a - b)

= tan(x + y - y)

= tan x

**This proves that (tan(x+y) - tan y)/(1 + tan(x+y)*tan y) = tan
x**

## See eNotes Ad-Free

Start your **48-hour free trial** to get access to more than 30,000 additional guides and more than 350,000 Homework Help questions answered by our experts.

Already a member? Log in here.